Juridical Ambiguity in Land Tenure: A Critical Analysis of Land Status Following Forest Area Relinquishment - Ghassani Irsia Khairina (Faculty of Law, Universitas Jenderal Soedirman, 2025)
Legal certainty in land tenure is fundamentally compromised by sectoral conflicts between agrarian and forestry law in Indonesia. A major issue is the juridical ambiguity of land status after a Forest Area Relinquishment Decree (Pelepasan Kawasan Hutan) is issued, often leading to disputes where these administrative decrees are contested by Certificates of Ownership (SHM). This research aims to analyze two key problems: 1) the essence and juridical status of land following a Forest Area Relinquishment Decree, and 2) the legal force of this Decree as land ownership evidence. This study employs a normative legal research methodology, which is qualitative, utilizing a statute approach and a descriptive-analytical specification based on library research of primary, secondary, and tertiary legal materials. The results demonstrate that land post-relinquishment becomes State Land within an Other Use Area (APL), and the Decree is legally recognized as a